Using national administrative data to understand placement stability for children in children’s homes in England - Hood, Rick; Goldacre, Allie (International Journal of Population Data Science, 2025)
Objectives This paper will present findings from a study of administrative data on children in children’s homes. Objectives were to identify the factors associated with more stable placements for children in children’s homes, and use these findings to understand the role of children’s homes in the care system as a whole. Methods In partnership with Ofsted, the inspectorate for children’s social care, we assembled an anonymised dataset linking routinely collected administrative data on children who had at least one placement in a children’s home (CH) in England between 2015-23. Analysis focused on the cohort of children who turned 18 in 2022/23 and their care history since birth (n=2,780). Our primary measure of stability was the number of placement moves during the child’s period of care following their first CH placement. Regression models were estimated to examine the association of stability with co-variates, including demographic characteristics, assessed needs, and other aspects of social care provision. Results Children had an average of 2.55 placement changes per 1,000 care days following a children's home placement. Female children had a higher placement instability than males. Children from Asian backgrounds had lower placement instability than White British children. Children who had more placements prior to entering a children’s home were more likely to experience subsequent placement changes. Higher levels of instability were associated with children who were assessed at risk of harms outside the home, who entered care under police protection, placed further from home, or placed on their own. Children in a children’s home with lower inspection outcomes tended to have higher placement instability. More placement moves were associated with higher rates of youth justice involvement, substance misuse, and going missing from care. Conclusion The findings suggest some groups of children in care encounter high levels of placement change both before and after entering a CH. Instability is associated with quality and outcome indicators for children in care, which reflects a growing problem with sufficiency in the sector.